Dementia awareness in Southern Switzerland among older adults: Health services research / Policy and plans. (7th December 2020) - Fadda, Marta; Fiordelli, Maddalena; Ibnidris, Aliaa; Franscella, Giovanni; Albanese, Emiliano
Abstract: Background: Public awareness of dementia is at the core of the WHO global action plan on the public health response to dementia. Evidence on dementia awareness in cognitively healthy older adults is limited. We measured dementia awareness, acceptance and understanding in a large sample of elders living in the Italian‐speaking part of Switzerland. Method: Between September and December 2019, 1, 364 older adults (65 years or more) living in Ticino were invited to participate in an online survey. We collaborated with a large local association of older adults (Associazione Ticinese Terza Età, ATTE) to recruit participants, and to translate and adapt the Dementia Knowledge Assessment Scale (DKAS), a 25 items Likert scale designed to measure knowledge of dementia from a biomedical perspective. The DKAS was previously validated, its score ranges between 0 and 50. Result: 628 men and women aged 65 to 97 (Mean: 73.3; Standard Deviation: 5.6) participated in the survey. Of these, 61.7% were women, 85.6% were highly educated (baccalaureate and above), and 75.4% retired. 42% of respondents believed that dementia is part of the normal ageing. DKAS scores varied markedly (Mean: 17.7; Standard Deviation: 6.9; range=1‐40), were higher for women (p<0.001), younger (p=0.031) and more educated (p=0.042) participants. Conclusion: The misconception that dementia is an ineluctable part of ageing was common, and level of dementia awareness markedly varied and was generally low in a large sample of elderly people living in the Italian‐speaking Canton of Switzerland. Our results have important implications for future actions and campaigns to raise awareness about dementia and to assess its effects.